Depreciation-Future Services Basis. - Young, T. N.; Peirson, C. G. (The Accounting Review, 1967)
Abstract This article focuses on the conventional methods of calculating depreciation often involve the arbitrary allocation of the historical cost of a fixed asset. The use of discounted cash-flow techniques has been advocated by a number of authors as the ideal basis for allocating the cost of an asset over its useful life. In the latter method, depreciation is regarded as the periodic reduction in the value of a fixed asset arising from a change in the asset's expected future benefits. Briefly, this method requires that the estimated future net services of the asset, including the scrap value, be discounted to their present value at the end of each accounting period. The future net services of an asset are the cash inflows of the business attributable to the use of that asset alone, that is, not attributable to other outlays, for example, for labor, materials, and maintenance or repair. This article examines the implications of changes in expectations for depreciation, first, when the discount rate is the internal rate and, second, when it is an external rate such as the cost of capital.